Effects of an immunosuppressive therapy on the efficacy of immune checkpoint inhibition in metastatic melanoma: an analysis of the prospective skin cancer registry ADOREG - Kochanek, Corinna; Gilde, Catharina; Zimmer, Lisa; Ugurel, Selma; Meier, Friedegund; Utikal, Jochen; Pföhler, Claudia; Herbst, Rudolf; Haferkamp, Sebastian; Welzel, Julia; Dücker, Pia; Leiter, Ulrike; et al. (European journal of cancer, 2024)
Background - The impact of immunosuppressive therapy (IST) on immune-checkpoint inhibition (ICI) is unclear. - Methods - Patients with unresectable advanced melanoma (MM) treated with ICI in the years 2011-2020 were identified from the prospective multicenter German skin cancer registry ADOREG. Patients with IST within 60 days before, or within 30 days after start of ICI were compared to patients without IST. End points were disease control rate (DCR), overall survival (OS) and progression-free survival (PFS) determined by Kaplan-Meier method. Prognostic factors were evaluated in a Cox regression model. - Results - Of 814 patients treated with ICI, 73 (9%) received concomitant IST, mainly steroids. Patients with brain metastases (BM) received IST more frequently (n = 34/130 patients; 26%), than patients without BM (39/684 patients; 6%). In patients without BM, IST initiated before, but not IST initiated after start of ICI was significantly associated with worse PFS (univariate hazard ratio (HR) 2.59, 95% confidence interval (95%-CI) 1.07-6.28, p = 0.035; multivariate HR 3.48, 95%-CI 1.26-9.6, p = 0.016). There was no association between IST and OS or DCR. In patients with BM, IST initiated before, but not after start of ICI was significantly associated with worse OS (univariate HR 2.06, 95%-CI 1.07-3.95, p = 0.031; multivariate HR 5.91, 95%-CI 1.74-20.14, p = 0.004). There was no association between IST and PFS or DCR. - Conclusion - Patients receiving IST 60 days before start of ICI showed a tendency to an impaired therapy outcome. IST initiated within 30 days after start of ICI, mainly due to early side effects, did not affect the efficacy of ICI therapy.
Gesehen am 17.03.2025
Online verfügbar: 28. Dezember 2023, Artikelversion: 5. Januar 2024